Contribution of dangling-bonds to polycrystalline SiC corrosion. (November 2020) - Kondo, Sosuke; Seki, Kotaro; Maeda, Yuki; Yu, Hao; Fukami, Kazuhiro; Kasada, Ryuta
Abstract: The relationship between lattice defects and the corrosion of SiC irradiated with heavy ions at 400 °C and 800 °C was investigated using electrochemistry and electron spin resonance spectroscopy. An immersion test in high-pressure hot water was also used to evaluate surface recession. The corrosion current increased monotonically with dangling-bond (DB) density, indicating that DBs were the primary reaction sites. Further, the surface recession rate in hot water increased exponentially with increasing DB density. The dense DBs were found to be surrounded by distorted lattices. These findings indicated that SiC dissolution was further accelerated by the accumulated lattice distortion. Graphical abstract: Image, graphical abstract